Loading rate effects on dynamic out-of-plane yarn pull-out. Issue 16 (October 2014) - Guo, Zherui; Hong, Jihye; Zheng, James; Chen, Weinong
In this study, the mechanical response of a single yarn pull-out from single layers of Kevlar® and Twaron® fabric under out-of-plane loading at both quasi-static and dynamic rates was experimentally investigated. In order to perform the dynamic experiments, a pendulum impact setup was designed and constructed to pull out a single yarn dynamically. The pull-out load was measured directly by a load cell and the movement of the fabric was measured to portray the load–displacement history. The effects of transverse pressure, different weave direction, and loading rates were also investigated.